Edukasi Manajemen Pembiayaan Pendidikan Islam Pada Masyarakat Pedamaran, Ogan 2 Komering Ilir - Ivan Riyadi; Subri Hasan (Universitas Islam Negeri Sumatera Utara, 2020)
Pedamaran is a subdistrict in the district of Ogan Komering Ilir, South Sumatera. Its inhabitants are comprised of Penesak and lake-clan tribes. The language is a Penesak language. Penesak is a language that is also equivalent to the Ogan language. Scattered in the area of Meranjat, Tanjung Batu, and base of the fortress. Population 45,448 people with Islamic religion99.9 percent. With society's potential of the Muslim majority, it is appropriate to do social service on Islamic education financing. Islamic education financing is managed with the accuracy of education financing management. This is a strategic concept to assist in absorbing the budget of Madrasah and how to manage the school's finances appropriately. From this social service, we hope that Islamic education institutions can be more advanced, especially in rural areas.